Efficient ethylene/ethane separation through ionic liquid-confined covalent organic framework membranes. Issue 10 (16th February 2022) - Liang, Xu; Wu, Hong; Huang, Hongliang; Wang, Xiaoyao; Wang, Meidi; Dou, Haozhen; He, Guangwei; Ren, Yanxiong; Liu, Yutao; Wu, Yingzhen; Wang, Shaoyu; Ge, Huilin; et al.
Abstract : For the first time, we demonstrate the utilization of covalent organic framework (COF) membranes for efficient ethylene/ethane separation. Abstract : Organic framework materials, owing to the long-range ordered channels, uniform channel sizes and readily tailored functionalities, are expected to become next generation membrane materials for molecular separations. In this study, for the first time, we demonstrate the utilization of covalent organic framework (COF) membranes for efficient ethylene/ethane separation. The COF membranes are loaded and modified with a silver ion-containing ionic liquid layer. Owing to the distinct confinement effects, the membrane channel size is first reduced by the physically absorbed ionic liquid and further reduced by the chemically bound ethylene molecules. When the membrane channel size is tuned to 0.87 nm, which is still larger than both ethylene (0.42 nm) and ethane (0.44 nm) molecules, an extraordinarily high ethylene/ethane selectivity up to 120 and ethylene permeance of 135 GPU are achieved simultaneously, which surpass most of the state-of-the-art membranes towards ethylene/ethane separation. Our strategy was also validated by propylene/propane separation. Moreover, the COF membranes exhibit superior chemical stability and long-term operation stability. Strikingly, our strategy opens a novel path for enabling membranes with larger pore/channel sizes for separating smaller molecule mixtures.